Automatic system for monitoring gaseous concentration in a packed-bed solid-state cultivation bioreactor - Henrique, João Paulo [UNESP] (2022)
In this work, the respiration gases were sampled from a packed-bed bioreactor used for solid-state cultivation (SSC) using different gas-sampling procedures. As a case study, Myceliophthora thermophila I-1D3b was cultivated at 45 °C in a mixture of sugarcane bagasse/wheat bran (7:3 w/w). Respiration gases were sampled at the top of the column (end-do-end mode) and in three other alternatives of sampling gases. Axial temperature profiles were obtained during the experiments and axial moisture contents and endoglucanase activities were determined after cultivation. The results showed that sampling gases at low flow rate produced similar results to the end-to-end operation. On the other hand, when part of the bed was subjected to inefficient aeration, the process was strongly affected in terms of accumulated gas concentrations and temperature. From the results, it was possible to infer some aspects of the microbial respiratory activity, which will be of help to SSC packed-bed bioreactor developers.